O direito à memória em face das violências autoritárias: os riscos e os desafios da (re)construção do passado a partir das possibilidades jurídicas e perspectivas éticas da memória - Santos, Dailor dos (Universidade do Vale do Rio dos Sinos, 2010)
The present study analyses the risks and challenges for attributing senses to the right to memory. It starts from the remembrance of violent practices accepted by the dictatorial regime that took power in Brazil from 1964 to 1985 to examine the distinctions between violence and power and elucidate the political and juridical repercussions of amnesty built in Brazil in 1979. It searches the link between history and memory, discusses the transdisciplinary format of memory, points its political underbelly and outlines its sociological conformation. It examines the juridical prospects of memory from the difficulties and risks of its claim as a right. It analyses the links between memory and truth, points the ethical foundation that allows the juridical construction of memory and encounters the paradoxes of the right to memory when it is confronted by the idea of a possible forgiveness, by the imposition of forgetfulness, by deficient understandings that law provides and by the requirements of transitional justice. The approach to this problem is phenomenological methodology. The study suggests that violence and power differ in their aspirations and in their possibilities. It states that violence committed by the Brazilian military dictatorship is the paradigm of barbarism in Brazil. It asserts that the political amnesty proposed in 1979 is not completed or overcome. It considers that memory, authentic political practice, emerges as present time?s answer to the violence of the past and as an appeal from all victims. It accepts a joint construction of history and memory. It visualizes the transdisciplinarity of memory. It understands memory in its reference to social belonging. It questions and informs the risks of the correlation between memory and truth. It recognizes the time of memory - concerned about all victims of the progress of history - as the ethical perspective for the construction of the right to memory. It accepts the possibility of a forgiveness built by the shared exercise of the right to memory. It points the limits for political amnesties and repels the idea that forgetfulness can be imposed. It refutes the position of the Brazilian Constitutional Court on the 1979 amnesty. It values the transitional justice practices and argues that the right to memory contributes to the consolidation of Human Rights. It proposes a self-criticism of law itself, from the dynamics of a fraternal law.
Keywords: Direito à memória; Poder e violência; Ética e memória; Direito fraterno; Justiça de transição; Right to memory; Power and violence; Ethics and memory; Fraternal law; Transitional justice; ACCNPQ::Ciências Sociais Aplicadas::Direito